A meta-analysis of factors influencing concentrations of brominated flame retardants and organophosphate esters in indoor dust. (15th September 2021) - Al-Omran, Layla Salih; Harrad, Stuart; Abou-Elwafa Abdallah, Mohamed
Abstract: Current assessments of human exposure to flame retardants (FRs) via dust ingestion rely on measurements of FR concentrations in dust samples collected at specific points in time and space. Such exposure assessments are rendered further uncertain by the possibility of within-room and within-building spatial and temporal variability, differences in dust particle size fraction analysed, as well as differences in dust sampling approach. A meta-analysis of peer-reviewed data was undertaken to evaluate the impact of these factors on reported concentrations of brominated flame retardants (BFRs) and organophosphate esters (OPEs) in dust and subsequent human exposure estimates. Except for a few cases, concentrations of FRs in elevated surface dust (ESD) exceeded significantly those in floor dust (FD). The implications of this for exposure assessment are not entirely clear. However, they imply that analysing FD only will underestimate exposure for adults who likely rarely ingest floor dust, while analysing ESD only would overestimate exposure for toddlers who likely rarely ingest elevated surface dust. Considerable within-building spatial variability was observed with no specific trend between concentrations of either BFRs or OPEs in living rooms and bedrooms in the same homes, implying that exposure assessments based solely on sampling one room are uncertain. Substantial differences in FR concentrations were observed in different particle size fractions of dust. This is likely partly attributable to the presence of abraded polymer particles/fibres with high FR concentrations in larger particle size fractions. This has implications for exposure assessment as adherence to skin and subsequent FR uptake via ingestion and dermal sorption varies with particle size. Analysing dust samples obtained from a householder vacuum cleaner (HHVC) compared with researcher collected dust (RCD) will underestimate human exposure to the most of studied contaminants. This is likely due to the losses of volatile FRs from HHVC dust over the extended period such dust spends in the dust bag. Temporal variability in FR concentrations is apparent during month-to-month or seasonal monitoring, with such variability likely due more to changes in room contents rather than seasonal temperature variation. Graphical abstract: Image 1 Highlights: FR concentrations vary significantly between floor and elevated surface dust. FR contamination of floor dust can vary significantly by within-room and within-building spatial variability. The most suitable dust size fraction for exposure assessment is < 150 μm.